Bile acids increase steroidogenesis in cholemic mice and induce cortisol secretion in adrenocortical H295R cells via S1PR2, ERK and SF‐1. (17th February 2019) - Liu, Lei; Panzitt, Katrin; Racedo, Silvia; Wagner, Martin; Platzer, Wolfgang; Zaufel, Alex; Theiler‐Schwetz, Verena; Obermayer‐Pietsch, Barbara; Müller, Helmut; Höfler, Gerald; Heinemann, Akos; Zollner, Gernot; et al.
Abstract: Background and Aims: Bile acids are now accepted as central signalling molecules for the regulation of glucose, amino acid and lipid metabolism. Adrenal gland cortex cells express the bile acid receptors farnesoid X receptor (FXR), the G protein‐coupled bile acid receptor (TGR5) and the sphingosine‐1‐phosphate receptor 2 (S1PR2). We aimed to determine the effects of cholestasis and more specifically of bile acids on cortisol production. Methods: FXR and TGR5 knockout mice and controls were subjected to common bile duct ligation (CBDL) or chenodeoxycholic acid (CDCA) feeding to model cholestasis. Human adrenocortical H295R cells were challenged with bile acids for mechanistic studies. Results: We found that CBDL and CDCA feeding increased the levels of corticosterone, the rodent equivalent to human cortisol and mRNA and protein levels of steroidogenesis‐related enzymes in adrenals independent of FXR and TGR5. Taurine‐conjugated CDCA (TCDCA) significantly stimulated cortisol secretion, phosphorylation of extracellular signal‐regulated kinase (ERK) and expression of steroidogenesis‐related genes in human adrenocortical H295R cells. FXR and TGR5 agonists failed to induce cortisol secretion in H295R cells. S1PR2 inhibition significantly abolished TCDCA‐induced cortisol secretion, lowered phosphorylation of ERK and abrogated enhanced transcription of steroidogenesis‐related genes in H295R cells. Likewise, siRNA S1PR2 treatment reduced the phosphorylation of ERK and cortisol secretion. Steroidogenic factor‐1 (SF‐1) transactivation activity was increased upon TCDCA treatment suggesting that bile acid signalling is linked to SF‐1. Treatment with SF‐1 inverse agonist AC45594 also reduced TCDCA‐induced steroidogenesis. Conclusions: Our findings indicate that supraphysiological bile acid levels as observed in cholestasis stimulate steroidogenesis via an S1PR2‐ERK‐SF‐1 signalling pathway.